Global Financial Stability Report, April 2009 : Responding to the Financial Crisis and Measuring Systemic Risks. (Global Financial Stability Report; Global Financial Stability Report, 2009)
The Global Financial Stability Report identifies potential fault lines in the global financial system that could lead to crisis, while providing comprehensive coverage of mature and emerging financial markets. The GFSR focuses on current conditions in global financial markets, highlighting issues that could pose risks to financial market stability and market access by emerging market borrowers.